Novel Insights into the Role of Caveolin-2 in Cell- and Tissue-Specific Signaling and Function - Grzegorz Sowa (Biochemistry Research International)
Caveolin-2 is one of the major protein components of cholesterol- and glycosphingolipid-rich flask-shaped invaginations of plasma membrane caveolae. A new body of evidence suggests that caveolin-2 plays an important, and often more direct, role than caveolin-1 in regulating signaling and function in a cell- and tissue type-specific manner. The purpose of this paper is to primarily focus on discussing how these recent discoveries may help better understand the specific contribution of caveolin-2 to lipid raft- and caveolae-regulated cell/tissue-specific signaling and functions.